Prevalence of stable and successfully treated periodontitis subjects and incidence of subsequent tooth loss within supportive periodontal care: A systematic review with meta‐analyses - Rattu, Varkha; Raindi, Devan S.; Antonoglou, Georgios N.; Nibali, Luigi (Journal of clinical periodontology, 2023)
To identify (i) the prevalence of meeting the endpoints of 'stable periodontitis' (probing pocket depth [PPD] ≤ 4 mm, bleeding on probing [BoP] < 10%, no BoP at 4 mm sites), 'endpoints of therapy' (no PPD > 4 mm with BoP, no PPD ≥ 6 mm), 'controlled periodontitis' (≤4 sites with PPD ≥ 5 mm), 'PPD < 5 mm' and 'PPD < 6 mm' at the start of supportive periodontal care [SPC]) and (ii) the incidence of tooth loss in relation to not meeting these endpoints within a minimum of 5 years of SPC. Systematic electronic and manual searches were conducted to identify studies where subjects, upon completion of active periodontal therapy, entered into SPC. Duplicate screening was performed to find relevant articles. Corresponding authors were contacted to confirm inclusion and retrieve required clinical data for further analyses to assess the prevalence of reaching endpoints and incidence of subsequent tooth loss, if available, within at least 5 years of SPC. Meta-analyses were carried out to evaluate risk ratios for tooth loss in relation to not reaching the various endpoints. Fifteen studies including 12,884 patients and 323,111 teeth were retrieved. Achievement of endpoints at baseline SPC was rare (1.35%, 11.00% and 34.62%, respectively, for 'stable periodontitis', 'endpoints of therapy' and 'controlled periodontitis'). Less than a third of the 1190 subjects with 5 years of SPC data lost teeth-a total of 3.14% of all teeth were lost. Statistically significant associations with tooth loss, at the subject-level, were found for not achieving 'controlled periodontitis' (relative risk [RR] = 2.57), PPD < 5 mm (RR = 1.59) and PPD < 6 mm (RR = 1.98). An overwhelming majority of subjects and teeth do not achieve the proposed endpoints for periodontal stability, yet most periodontal patients preserve most of their teeth during an average of 10-13 years in SPC.